The Potential of CO2 Incubator "Sriwijaya CO2 Incubator" Against Cell Culture Proliferation In Invitro Study As Smart Controlling-Based CO2 Incubator For Cell Culture - Wardiansyah; Rachmat Hidayat; Msy Rulan Adnindya (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
A B S T R A C TIntroduction. A CO 2 incubator is an essential tool for the initiation of theproliferation of primary culture cells or cell lines. In principle, this tool works bykeeping the sample cell line at an optimum temperature of 37 o C and 5% carbondioxide supply. The ability of the CO 2 incubator to maintain temperature and supplyof 5% carbon dioxide are essential points in the development of the CO 2 incubator.This study is an attempt to convince the potential of Sriwijaya CO 2 Incubator inmaintaining the proliferation ability of cultured cells in an in vitro study. Methods.This study is an experimental pre-post test that explores the percentage of viabilityof primary culture cells (fibroblasts) before and after incubation in CO 2 incubators.The object of this study was fibroblast cells obtained from the prepuce of patientswho performed circumcision. Results. Fibroblast cell proliferation in CO 2 incubatorsshows an increase in the number of fibroblast proliferation which can be seen withthe increasing number of cells visualized by inverted microscopy. Conclusion.Sriwijaya CO 2 incubator has the potential to be used in in vitro research to triggerthe growth and proliferation of fibroblast cells.